2020
DOI: 10.1002/jor.24684
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of the anterior cruciate ligament following primary repair with internal bracing: A longitudinal study

Abstract: Diffusion tensor imaging (DTI) provides information about tissue microstructure and its degree of organization by quantifying water diffusion. We aimed to monitor longitudinal changes in DTI parameters (fractional isotropy, FA; mean diffusivity, MD; axial diffusivity, AD; radial diffusivity, RD) of the anterior cruciate ligament (ACL) following primary repair with internal bracing (IBLA). Fourteen patients undergoing IBLA were enrolled prospectively and scheduled for clinical follow‐up, including instrumented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…DTI results are different from conventional MRI, as DTI provides information about tissue microstructure and its degree of organization by quantifying water diffusion. Their findings suggest that healing of the ACL is incomplete at 24 months post‐operatively [6]. We observed overall poor ACL healing on MRI in six (19.4%) of our study patients during the 2‐year follow‐up.…”
Section: Discussionmentioning
confidence: 57%
“…DTI results are different from conventional MRI, as DTI provides information about tissue microstructure and its degree of organization by quantifying water diffusion. Their findings suggest that healing of the ACL is incomplete at 24 months post‐operatively [6]. We observed overall poor ACL healing on MRI in six (19.4%) of our study patients during the 2‐year follow‐up.…”
Section: Discussionmentioning
confidence: 57%
“…20-23 Recently, DTI and tractography have been developed to study the complex collagen fiber structures of connective tissues in knee joint. 24,25 Compared with T2 and QSM, DTI estimates the fiber direction by detecting the signal decay at different diffusion gradient directions with no need to physical rotate the specimen or subject. 26-30 Diffusion tractography of the anterior cruciate ligament (ACL) graft has been proved to be feasible on clinical 3-T MRI scanners and can provide a reliable estimation of quantitative diffusion indices of the ACL graft.…”
Section: Introductionmentioning
confidence: 99%
“…Dyck et al demonstrated the feasibility and reliability of DTI for the visualization and quantitative evaluation of the ACL graft using a clinical 3T system 77 . DTI provided objective biomarkers to assess graft healing following ACL reconstruction to guide the time of return to sports 77–79 . The zonal‐dependent DTI metrics (FA, MD, axial, and transversal diffusivity) of the porcine meniscus have been recently reported using a 3D DW‐SE sequence 80 .…”
Section: Musculoskeletal Applications Of Quantitative Diffusionmentioning
confidence: 99%
“…77 DTI provided objective biomarkers to assess graft healing following ACL reconstruction to guide the time of return to sports. [77][78][79] The zonal-dependent DTI metrics (FA, MD, axial, and transversal diffusivity) of the porcine meniscus have been recently reported using a 3D DW-SE sequence. 80 The complex collagen fiber architecture of the entire meniscus can be resolved by diffusion tractography.…”
Section: Ligaments Tendons and Meniscimentioning
confidence: 99%